(untitled) (Sociologisk Forskning, 2024)
Building from debates about academic capitalism and universities’ adaptation to surrounding society, this article analyzes the vision and strategy documents of Swedish universities. Using Bacchi’s What’s the problem represented to be approach, we analyze how and to what extent such documents advocate for the adaptation of universities’ activities to the demands of surrounding society and market economy, and the societal and institutional problems such adaptation processes are considered to counteract. In all documents we find an externalization imperative, where universities plan for an adjustment of activities to the demands and interests of external actors. Primarily, this applies to their advocacy of a utility ideal, promoting the instrumentalization of knowledge and its transformation into tools for external actors’ goals and purposes. This adaptation process is partly articulated as responding to the allegedly problematic aspects of previous university ideals, understood as characterized by introspection and exclusion, partly as responding to overarching “societal challenges”, understood through sustainability discourse. In the article, we discuss these problem representations critically, contextualizing them in relation to knowledge capitalism and the postmodernization of knowledge.